24. VACCINATION RATE AND INTENDED VACCINATION OF PNEUMONIC VACCINATION IN ADULTS AND SOME RELATED FACTORS AT THE VACCINATION CLINIC OF HANOI MEDICAL UNIVERSITY, 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the vaccination rate and intention to vaccinate against pneumococcus in adults and some related factors.Research method: Cross-sectional descriptive study on 268 adults aged 18 years and older who came to the Vaccination Room 2, Hanoi Medical University.Results: The proportion of adults who have been vaccinated against pneumococcus is only 11.5%. Among those who have not been vaccinated, 64.4% intend to be vaccinated in the future and this decision is mainly due to receiving advice from doctors. Young people (under 30 years old), those with high school education or higher, and those who are single have the intention to be vaccinated against pneumococcus 1.93 times, 11.57 times, and 1.93 times higher than others, respectively (p
Keywords: pneumococcal vaccine, vaccination, intended, adult.